Evaluation Of The Subclavicular Route For The Pectoralis Major Flap In Oral And Maxillofacial Reconstruction-Our 15 Years Experience - Ata Garajei; Ali Arab Kheradmand; Azadeh Emami (Journal of Craniomaxillofacial Research, 2024)
Introduction: The pectoralis major flap (PMF) is an important reconstructive tool for defects in the head and neck region but excessive bulk and a limited arc of rotation can be problematic. These problems can be addressed by passing the pedicle deep to the clavicle but some authors feel that this modification may compromise the vitality off the flap. In the current article, these problems have been addressed by using a modified method. Materials and Methods: During the past 15 years (2000 to 2014) 182 head and neck cancer patients were treated for primary reconstruction following tumor ablation. PMF was modified by passing the pedicle deeply to the clavicle. Following flap harvest, the pedicle was passed in the subclavicular plane for reconstruction. Results: It was possible to increase the average length of PMF to 2.5-3.5cm compared to the supraclavicular route by using this modification. Minor complications were observed in 9 of 182 cases (5%): Partial flap necrosis occurred in 6 cases and fistula formation was observed in 3 cases. Conclusion: The subclavicular route increases the length and arc of rotation without compromising vascular supply to a higher degree compared to the conventional supraclavicular route. Furthermore, this concept decreases the bulk of the flap pedicle which is functionally and cosmetically favourable. Keywords: Pectoralis major flap; Subclavicular route; Head and neck reconstruction; Pedicle flap.